2018
DOI: 10.1002/jcb.26650
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of serum exosomal miR‐638 predict poor prognosis in hepatocellular carcinoma

Abstract: Currently available studies have implicated that exosome-delivered microRNAs (miRNAs) play crucial roles in human cancer. However, the association of serum exosomal miR-638 and hepatocellular carcinoma (HCC) remains largely unknown. We aim to investigate the expression of exosomal miR-638 in serum of HCC patients and its prognostic role in this deadly disease. Kaplan-Meier and Cox regression analyses were used to determine the survival of patients histologically diagnosed with HCC. Reduced levels of exosomal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 32 publications
3
85
0
3
Order By: Relevance
“…MiR-16 levels were used for normalization based on previously published results. 15,19 We found that the levels of exosomal miR-122, miR-125b, miR-145, miR-192, miR-194, miR-29a, miR-17-5p, and miR-106a were significantly upregulated in HCC patient serum. In addition, these exosomal miRNAs except miR-145 yielded AUC of 0.650 to 0.850 for discriminating HCC from healthy subjects ( Figure 2).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…MiR-16 levels were used for normalization based on previously published results. 15,19 We found that the levels of exosomal miR-122, miR-125b, miR-145, miR-192, miR-194, miR-29a, miR-17-5p, and miR-106a were significantly upregulated in HCC patient serum. In addition, these exosomal miRNAs except miR-145 yielded AUC of 0.650 to 0.850 for discriminating HCC from healthy subjects ( Figure 2).…”
Section: Discussionmentioning
confidence: 92%
“…We first assessed the exosomes isolated from the serum. Transmission electron microscopy revealed spherical vesicles approximately 40 to 100 nm in diameter of all samples (Figure S1A), which is consistent with previous description of exosomes . We also performed Western blot analysis to detect 2 commonly used exosomal protein markers, namely, CD9 and CD63.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, exosomal miR-665 levels were elevated in larger tumours with local invasion Serum extracellular vesicles [30] and at an advanced clinical stage (stage III/IV) of HCC [40] . Another study found decreased expression of serum exosomal miR-638 in HCC patients [41] . High miR-1247-3p in serum exosomal levels correlated with lung metastasis, poor overall survival and poor disease-free survival in HCC patients [19] .…”
Section: Exosomal Rna Biomarkersmentioning
confidence: 97%
“…43 Furthermore, there are several studies regarding the diagnostic potential of circulating exosomal microRNAs in HCC including miR-21, 44 miR-125b,45 and miR-638 46. Furthermore, we need to explore the therapeutic potential of miR-92b targeted therapy for future preclinical and clinical applications.In addition to the functional analysis of exosomal miR-92b in tumor cell biology and tumor immunity, we have clarified the beneficial impact of circulating exosomal miR-92b for early prediction of posttransplant HCC recurrence (Figures 5 and 6).…”
mentioning
confidence: 99%